Long-Term Effectiveness and Safety of Ixekizumab for the Treatment of Moderate-to-Severe Plaque Psoriasis: A Five-Year Multicenter Retrospective Study-IL PSO (Italian Landscape Psoriasis) - Mario Valenti; Luigi Gargiulo; Luciano Ibba; Piergiorgio Malagoli; Fabrizio Amoruso; Anna Balato; Federico Bardazzi; Martina Burlando; Carlo G. Carrera; Paolo Dapavo; Valentina Dini; Francesca M. Gaiani; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction The introduction of biological therapies has revolutionized the treatment of moderate-to-severe plaque psoriasis. In particular, ixekizumab, an inhibitor of interleukin-17A, has shown great results in terms of efficacy and safety in both clinical trials and real-world experiences. However, there is a lack of long-term real-world data available for ixekizumab. Methods We conducted a multicenter real-life study to evaluate the effectiveness and safety of ixekizumab in patients with moderate-to-severe plaque psoriasis. Psoriasis Area and Severity Index score (PASI) was collected at baseline and after 1, 2, 3, 4, and 5 years. The occurrence of any adverse events was recorded at each time point. Results We enrolled 1096 patients treated with ixekizumab for at least 1 year. At week 52, the percentages of PASI 90 and PASI 100 were 85.04% and 69.07%, respectively. After 5 years of treatment with ixekizumab, out of 145 patients, a PASI 90 response was achieved by 86.90% of patients, while complete skin clearance was reached by 68.28% of patients. We did not observe any new significant safety findings throughout the study period. Conclusion This study supports the long-term effectiveness and safety of ixekizumab in a real-world setting.